Propofol-loaded nanomicelle with improved anesthetic, pharmacokinetic, hemocompatibility, safety, and permeation profiles - Hongfei Chen; Long He; Da Li; Feng Jin; Yanqiu Ai (Arabian Journal of Chemistry, 2021)
Propofol is known as one of the most potential anesthetics which suffer from limited duration of anesthesia water insolubility. Therefore, in the present study, a formulation of propofol- carboxylic acid-poly [ethylene glycol (COO-PEG)]-b-poly[ D,L lactide (PDLA)]-nanomicelle was developed and its characterization was done by transmission electron microscopy (TEM) and dynamic light scattering analysis (DLS) studies. Afterwards, drug release assay was carried out to determine the efficacy of COO-PEG-PLDA nanomicelle in drug delivery systems. Cytotoxic, hemolytic, pharmacokinetic, and permeation assays were also followed by anesthetic efficacy of propofol- COO-PEG-PLDA nanomicelle in the rat hind paw model. The results indicated that the diameter, hydrodynamic radius and zeta potential of fabricated drug-loaded nanomicelles were 30 nm, 73.24 nm and –23.59 mV, respectively and the nanomicelles were stable for a period of 50 min. Also, COO-PEG-PLDA nanomicelle showed a sustained propofol release at physiological pH. Moreover, it was indicated that COO-PEG-PLDA nanomicelle reduced the cytotoxic and hemolytic effects of propofol and increased the steady-state flux (Jss) by 6.64 times (***P < 0.001) and the cumulative amount of propofol permeated per cm2 of esophageal epithelium after 5 h (Q5h) by 6.01 times (***P < 0.001). Furthermore, pharmacokinetic data showed that COO-PEG-PLDA nanomicelles provided several fold increases in plasma concentration of propofol compared to free propofol at different time intervals. Finally, it was shown that COO-PEG-PLDA nanomicelles improved the induction time of anesthesia, anesthesia period and walking time induced by propofol. In conclusion, it may be suggested that encapsulation of propofol into diblock copolymer nanomicelles can be developed as a new novel therapeutic strategy, facilitating future research as a topical anesthetic.